(3JMQjQ cJGH GdeSGcf dKGhPhSjhSs - (3bSWG Hf dhbG GdHYdHcj,J (B300 (3g` s
(3ChdgG (B:s
(3HYO G dHSedI hGdOjHGLI GdPjf eScfge JMJ GdbWH GdTeGdj afUa cQI Gdcd GdXGgQ dge ShGA jcf XGgQ dge HYjfg hfUagG GdNaj Yfge s
(3BNQgG (B:s
(3aEf ReGf JHOjd cd hGMOI efgG fUa GdcQI GdNaj GYXe ef ReGf JHOjd Gj bhS cGfJ fMQgG ef Pdc GdfUa s
(3Vef eLehY , JQJjHgG (B: 8s
(3HgG fXGe GdJYbjHIs
(3hgh (B112 (3Tcd gfOSjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B131s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs